Stress Analysis and Safety Implications of Aviation Oil Pipelines Under Soil Piling: A Numerical Simulation Study - Sharma, Arjun (Journal of Computer Science and Software Applications, 2025)
With the rapid development of the aviation oil industry, the safety of buried aviation oil pipelines under the influence of nearby soil piling has become a critical concern. This study investigates the stress response and deformation behavior of aviation oil pipelines subjected to soil piling through numerical simulation using ABAQUS software. The findings reveal that the maximum Mises stress in the pipeline increases significantly with decreasing soil pile distance and increasing pile height, exhibiting a near-linear relationship. Stress distribution patterns indicate that the middle section of the pipeline is most susceptible to damage, with stress symmetrically decreasing towards the ends. Results were validated against field tests, demonstrating the accuracy and applicability of the simulation approach in addressing engineering challenges. Preventive strategies are proposed to mitigate soil piling-induced stress and ensure the safe operation of aviation oil pipelines. This study provides valuable insights into the interaction between pipelines and surrounding soil, contributing to enhanced safety and reliability in pipeline management.